Factors on adoption of internet banking among UTM undergraduate students - Chang, Wei Lin, 1989-, author; Kamaruzzaman Abdul Rahim, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda (Perakaunan)) - Universiti Teknologi Malaysia, 2013